2016
DOI: 10.1089/chi.2015.0232
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Diet Behaviors and Measures of Glycemia, in Clinical Setting, in Obese Adolescents

Abstract: Objective: To determine the influence of dietary behaviors, assessed in a clinical setting, on measures of glycemia in overweight and obese adolescents.Study Design: The study is a retrospective, cross-sectional chart review. Eligible participants were overweight youth (N = 146, age 9-21 years) who attended the Youth Diabetes Prevention Clinic in Indianapolis, IN. Glycemic status was assessed during a 2-hour oral glucose tolerance test (OGTT). In the Bright Futures Questionnaire, a recommended clinical tool fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…47 The ADA recommends dietary strategies that reduce calories, and intake of dietary fat, and increase the intake of dietary fiber and foods containing whole grains, while limiting the intake of sugar-sweetened beverages.studies have pointed out the importance of dietary fibers of in daily meals. 49 Several studies have also pointed out unhealthy dietary habits, observed in adolescence.…”
Section: Improper Dietary Intakementioning
confidence: 99%
“…47 The ADA recommends dietary strategies that reduce calories, and intake of dietary fat, and increase the intake of dietary fiber and foods containing whole grains, while limiting the intake of sugar-sweetened beverages.studies have pointed out the importance of dietary fibers of in daily meals. 49 Several studies have also pointed out unhealthy dietary habits, observed in adolescence.…”
Section: Improper Dietary Intakementioning
confidence: 99%
“…Lifestyle behaviors of adolescents are characteristically low in amount of physical activity, and excessively sedentary, high in dietary intake of refined grains, saturated fats and added sugars, and low in intake of fruits and vegetables. Independent of obesity, these lifestyle factors may promote the risk of developing T2D [3640]. An intensive behavior modification program, demonstrated the efficacy of lifestyle intervention to improve nutrition and physical activity for reducing the risk of type 2 diabetes in adolescents, but it was conducted in the academic setting [11].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is associated with low consumption of fruits, vegetables and whole grains, excessive consumption of refined grains, saturated fats and added sugars, and high amounts of time spent in sedentary behavior [33–35]. In adolescents, we [36] and others [3739] have shown that high dietary intakes of fat as well as sugary foods and beverages are negatively associated with elevated glycemia and insulin resistance. Also, high sedentariness negatively influenced insulin secretion and sensitivity in youth [40].…”
Section: Introductionmentioning
confidence: 99%
“…To identify possible risk factors for prediabetes in adolescence, the risk factors for type 2 diabetes would be the most prominent. For example, sedentary lifestyle or lack of physical exercise (8), improper dietary intakes (9), obesity, and family history of diabetes are well documented as risk factors for type 2 diabetes (8). Among them, we focus on skipping breakfast as a risk factor for prediabetes in adolescence because it is prevalent among adolescents, for example, 8.0% in junior high school in Japan (10,11).…”
Section: Introductionmentioning
confidence: 99%